Effects of an exercise program in individuals with chronic low back pain - Zanini, Maurice (2014)
Introduction: Low back pain is a major cause of medical appointments, work disability and hospitalization. Aim: To measure changes in back pain scores and spinal functional capacity in individuals with low back pain after an exercise program. Methods: Non-randomized controlled trial of 40 participants (20 in the experimental group and 20 in the control group). Patients from both groups were evaluated before and after the program. The program consisted of flexibility training using joint mobilization and stretching exercises for the upper and lower limbs and back, as well as strength training for the abdominal muscles and hamstrings. Participants in the control group did not receive any exercise-related interventions, only medical care. Results: the experimental group showed significant improvements in pain score (P